Edukasi Deforestasi Dan Konservasi Lingkungan Bagi Kelompok PKK Di Desa Puraseda Dalam Mendukung SDG 13 Dan SDG 15 - I Nyoman Aji Suadhana Rai; Early Nalvi Hoata Sahureka; Ferdinand Marcel Pindonta Barus; Nazwa Nurcantika; Bintang Hafizh Setiawan (CV. Multi Kreasi Media, 2026)
Forest loss has consequences beyond the reduction of tree cover, as it can also weaken the role of vegetation in protecting soil and regulating water. Against this background, a community service activity was organized for members of the Family Welfare Empowerment (PKK) group in Puraseda Village, Leuwiliang District, Bogor Regency, with a focus on deforestation and environmental conservation. Held on 17 July 2026 under the IR-DEDICATE 2026 program, the activity involved 16 PKK members. The session included a presentation, a simple demonstration using two soil-surface models with different vegetation cover, a question-and-answer session, and educational games. The activity is reported descriptively on the basis of field observations, photographic documentation, and reflections from the organizing team. The demonstration allowed participants to observe differences between the two soil-surface models, while the discussion provided an opportunity to ask questions and respond to the material presented. In terms of the Sustainable Development Goals, the activity is most directly connected to SDG 15, particularly Target 15.2, through its emphasis on deforestation, vegetation functions, and conservation. Its relevance to SDG 13 is more limited, relating mainly to the educational dimension that overlaps with Target 13.3.